The systemic and financial legal bases of health care in Poland – selected issues - Elżbieta Feret (Prawo Budżetowe Państwa i Samorządu)
Protection of health is one of the basic public tasks performed for the benefit of citizens which is listed by the Constitution of the Republic of Poland. In this respect, every citizen of the Republic of Poland is guaranteed a right to receive benefits offered by the state and respective territorial self-government units. The purpose of these benefits is to ensure permanent and unrestricted access to the health care system. This access can only be provided on the basis of a properly organized system of financing the organizational units which perform health care tasks. Hence, it is of great importance not only to construct the entire system of health services, but also to guarantee adequate financial resources to each of the units operating in this area. In the light of the applicable laws in Poland, the legal acts which constitute not only the systemic but also the financial basis for the operation of health care, are very extensive and take the form of a number of separate legal regulations. This makes it very difficult to clearly and uniformly define the principles of financing public tasks in the realm of a health care. The problem in question becomes even more complicated when, in addition, numerous legal regulations allow for their implementation to be made also by private entities using public funds. In view of the above, the choice of the theme, in the opinion of the Author, is extremely important, but at the same time complicated, owing to technical limitations resulting from studies in the form of scientific articles. However, these thematic issues raised may serve as the basis for discussion and further, broader studies in this area, developed on the basis of the ever-changing legislation. Therefore, only two main issues will be indicated in this article. The first one is related to the functioning of public authorities in the area of healthcare at state and local government level, related to the definition of organizational and legal forms operating within the public finance sector. The second one, signals the possibility of healthcare implementation delivered by private entities, for which the legislator also provided the right to use budgetary resources in order to perform tasks within the healthcare sector.